2016
DOI: 10.4238/gmr.15038595
|View full text |Cite
|
Sign up to set email alerts
|

Pheno-morphological variation, genetic diversity and population structure of Tunisian Echinus Medic (Medicago ciliaris L.)

Abstract: ABSTRACT. Medicago ciliaris L., considered as a valuable genetic resource, is a good candidate for the improvement of marginal or degraded lands with low fertility or high salinity. In this study, the phenomorphological and genetic diversity were investigated in 14 Tunisian populations of M. ciliaris for the first time. Fourteen morphological traits showed significant differentiation between populations and high levels of diversity. Two amplified fragment length polymorphism primer combinations (E-AGC/M-CAA; E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…A negative correlation is present between flowering, 100 seed weight and 100 pod weight, meaning that larger pods and seeds are the early flowering ones. Those results are consistent with Berger et al (2002) and Jabri et al (2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A negative correlation is present between flowering, 100 seed weight and 100 pod weight, meaning that larger pods and seeds are the early flowering ones. Those results are consistent with Berger et al (2002) and Jabri et al (2016).…”
Section: Discussionsupporting
confidence: 93%
“…A positive correlation existed between days to flowering and the altitude. The findings are consistent with those obtained by Jabri et al 2016 for Tunisian Echinus Medic (Medicago ciliaris L.). As the temperature decreases at high elevations (Tranquillini 1964), this explains the negative correlation that existed between temperature and altitude.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we present the first report of molecular characterization of the M. intertexta populations and a comparison of their genetic diversity with M. ciliaris populations using SSR markers. Available information on the investigation of genetic diversity using molecular markers in M. ciliaris and M. intertexta is scarce; only one study has been published on the assessment and analysis of genetic diversity in M. ciliaris using microsatellite markers (Badri et al, 2007), another study analyzed the genetic diversity in M. ciliaris using AFLP markers (Jabri et al, 2016), and no molecular characterization was done on M. intertexta so far. The transferability rate of the studied SSR markers coming from the genome of M. truncatula to M. ciliaris and M. intertexta in this study is higher than the one that is found by Badri et al (2007).…”
Section: Discussionmentioning
confidence: 99%